Macroprolactinemia: a New Cause of Hyperprolactinemia - Naoki Hattori (Elsevier, 2003)
Hyperprolactinemia is not only seen in pregnancy but also in several pathological conditions such as prolactin (PRL) secreting pituitary adenoma (prolactinoma), intracranial tumors compressing the pituitary stalk or hypothalamus, and PRL stimulative drugs. However, some patients with hyperprolactinemia are diagnosed as having idiopathic hyperprolactinemia because the causes are unknown. They are subjected to repeated radiological examinations to find a microadenoma, to a long-term treatment with bromocriptine, and even to a surgical intervention. There is accumulating evidence that macroprolactinemia, in which most circulating PRL forms large protein complexes (more than 150 kDa), is a major cause of idiopathic hyperprolactinemia. The patients with macroprolactinemia are clinically characterized by the lack of hyperprolactinemia-related symptoms such as amenorrhea and galactorrhea. We found that anti-PRL autoantibody is a leading cause of macroprolactinemia that might be heterogeneous in nature. Most patients with anti-PRL autoantibodies were symptom-free and pregnancy was possible despite a marked hyperprolactinemia. Identification of macroprolactinemia is clinically important to prevent unnecessary examinations and treatments in patients with idiopathic hyperprolactinemia.